15q11.2 Duplication Encompassing Only the UBE3A Gene Is Associated with Developmental Delay and Neuropsychiatric Phenotypes. Issue 7 (July 2015) - Noor, Abdul; Dupuis, Lucie; Mittal, Kirti; Lionel, Anath C.; Marshall, Christian R.; Scherer, Stephen W.; Stockley, Tracy; Vincent, John B.; Mendoza‐Londono, Roberto; Stavropoulos, Dimitri J.
<x xml:space="preserve">Abstract</x> A duplication involving only the UBE3A gene was identified in a family with neuropsychiatric phenotypes. Family members with maternal inheritance of this duplication were found to have a broad range of phenotypes including autistic features, learning disability, schizophrenia, depression and anxiety.